Structural, Optical, and Renewable Energy-Assisted Photocatalytic Dye Degradation Studies of ZnO, CuZnO, and CoZnO Nanostructures for Wastewater Treatment - Khalid, Awais; Ahmad, Pervaiz; Memon, Roomia; Gado, Lamyaa F.; Khandaker, Mayeen Uddin *; Almukhlifi, Hanadi A.; Modafer, Yosra; Bashir, Najma; Abida, Otman; Alshammari, Fahdah Ayed; Timoumi, Abdelmajid (MDPI, 2023)
Renewable energy can be harnessed from wastewater, whether from municipalities or industries, but this potential is often ignored. The world generates over 900 km3 of wastewater annually, which is typically treated through energy-consuming processes, despite its potential for energy production. Environmental pollution is a most important and serious issue for all and their adulterations to the aquatic system are very toxic in very low concentrations. Photocatalysis is a prominent approach to eliminating risky elements from the environment. The present study developed Zinc oxide (ZnO), Copper-doped Zinc oxide (CuZnO), and Cobalt-doped Zinc oxide (CoZnO) nanostructures (NSs) by facile hydrothermal route. The crystalline and structural stability of the synthesized nanostructures were evident from XRD and FESEM analysis. Metal, and oxygen bond and their interaction on the surfaces and their valency were explored from XPS spectra. Optical orientations and electron movements were revealed from UV-Visible analysis. After 100 min exposure time with 1 g of catalyst concentration 60%, 70%, and 89% of dye degraded, for dye concentration (5 mg/L to 50 mg/L), the huge variation observed (70% to 22%), (80% to 16%), (94% to 10%). The highest photodegradation rate (55%, 75%, 90%) was observed on pH~12 using ZnO, CoZnO, and CuZnO respectively. Photodegradation of methylene blue confirmed the largest surface area, rate of recombination, photo-excited charge carriers, photo-sensitivity range, and radical generations of ZnO, CuZnO, and CoZnO. The present study, therefore, suggested that CuZnO would be preferred to produce nanomaterials for industrial wastewater treatment like methylene.